Constipation and other common symptoms reported by women and men in methadone and buprenorphine maintenance treatment. (1st December 2017) - Haber, Paul S.; Elsayed, Mahmoud; Espinoza, David; Lintzeris, Nicholas; Veillard, Anne-Sophie; Hallinan, Richard
Highlights: Opioid substitution treatment (OST) is often long-term. Therefore opioid-related symptoms are of interest. Few have reported opioid-related symptoms by gender. Men and women receiving OST reported similarly high rates of somatic symptoms. Somatic symptoms were highest in opioid users not receiving OST. Abstract: Background: Opioid substitution treatment (OST) is often continued long-term and, therefore, opioid-associated symptoms are of interest. Symptoms associated with methadone maintenance treatment (MMT) in men are well described, but there are fewer reports concerning symptoms associated with buprenorphine maintenance treatment (BMT) and very few reports among women. Method: Recipients of BMT (n = 113) and MMT (n = 184), non-opioid users (n = 105) and opioid users not receiving OST (n = 87) completed the Patient Assessment of Constipation (PAC-SYM) and a general symptom checklist. Multivariate analysis included other potential moderators of opioid-associated symptoms. Findings: Opioid users reported a higher frequency and severity of symptoms than non-opioid users. Constipation, dry mouth, decreased appetite, sweating and fatigue were highly prevalent in the previous 30 days (51–80%). Nausea, itchy skin, trouble urinating, menstrual problems, lightheadedness, blurred vision, heart racing were also common (30–50%). Non-OST opioid users had significantly higher frequency and severity than OST recipients of nausea, vomiting, diarrhoea, decreased appetite, sweating and itchy skin. Sweating was significantly more common in MMT than BMT. Constipation scores were higher in women, otherwise most sex differences were small. Higher PAC-SYM scores were associated with vomiting (OR = 1.04) and sweating (OR = 1.06). Cannabis use was associated with vomiting (OR = 2.19). Constipation (OR = 1.07), insomnia (OR = 2.5) and depression (OR = 2.82) were associated with fatigue. Conclusion: Men and women receiving OST report similarly high rates of somatic symptoms, though less than opioid users not receiving OST. There were few differences between BMT and MMT. Buprenorphine might be preferred where sweating is problematic. Several modifiable factors were identified.